Failure analysis of a Pelton impeller. (February 2015) - Chávez, J.C.; Valencia, J.A.; Jaramillo, G.A.; Coronado, J.J.; Rodríguez, S.A.
Highlights: The material presented defects like nonmetallic inclusions, microcracks and trapped silt. The CFD analysis permitted identifying low-pressure zones where cavitation is present. The finite element analysis permitted the identification of critical points on the bucket zone neck. Abstract: This paper presents the analysis of a 16-bucket Pelton impeller from a hydroelectric plant in Colombia, a plant with two turbo generators with a nominal capacity of 2.33 MW each. Multiple cracks were detected one year subsequent to geometry reconstruction welding repair. Metallographic analyses were performed on the impeller zones near the cracks, including an analysis of the fracture surface, a computational simulation of the fluid dynamics using finite volume software that permitted the establishment of the impeller's load state and a simulation via finite element analysis to determine the state of the impeller's nominal stress. It was concluded that the material presented multiple defects such as non-metallic inclusions and microcracks, and trapped slag was found in the filler material. The computational fluid dynamics analysis permitted the identification of low-pressure zones caused by an inadequate geometry for the bucket profile where cavitation is present. The finite element analysis permitted the identification of critical points on the bucket zone neck, coinciding with the crack found. This zone is under tensile stress due to the effects of centrifugal force and compression when the bucket comes in contact with the jet, causing fatigue.